An Investigation on the Effect of STEM Practices on Sixth Grade Students’ Academic Achievement, Problem Solving Skills, and Attitudes towards STEM - Müzdelife Kurt; Semra Benzer (Journal of Science Learning, 2020)
This study aims to identify the effect of STEM practices, integrated into Science courses in 6th grades of middle schools, on students' academic achievement, problem-solving skills, their attitudes towards STEM, and their interest level of STEM fields. The population of the study consists of 6th-grade students enrolled in a middles school in the 2018-2019 academic year. During the research, Academic Achievement Test, STEM Attitude Scale, STEM Career Interest Survey, and Problem Solving Inventory were applied to experimental and control groups as pre and post-tests by quasi-experimental research design. In data analysis, a statistics package program was used. Results of the study showed that the Academic Achievement Test scores of experimental groups that received STEM practices were seen to be higher than that of the control group to which the constructivist approach was applied. The difference was observed to be meaningful. Also, when the post-test scores of the STEM Attitude Scale, STEM Career Interest Survey, and Problem Solving Inventory were compared, a meaningful difference was found between the experimental and control group.